FACTORS OF APPLICATION FOR MARRIAGE ISBAT AT THE RELIGIOUS COURT OF SUNGGUMINASA GOWA - Salam, Abdul; Ridwan, Moh. Saleh; Maloko, M. Tahir (Program Pascasarjana, UIN Alauddin Makassar, 2021)
This paper discusses the factors for submitting an application for marriage isbat at the Gowa Sungguminasa Religious Court. This type of research is a descriptive qualitative field research. In this study, using primary, secondary and tertiary data sources. Furthermore, the data collection methods used were observation, interviews and documentation. Data processing and analysis techniques are carried out through three stages, namely: data reduction, data display, and conclusion drawing/vervication. The results of the study indicate that the main factor causing the parties to apply for Isbat Marriage at the Religious Court of Sungguminasa Gowa is the existence of urgent interests related to legal administration, for example taking care of veterans' benefits, taking care of their child's birth certificate. Therefore, it is expected that teenagers or prospective brides before deciding to get married should have knowledge about marriage, knowledge of building a good household according to Islamic teachings, and ensure all administration related to marriage is completed first, because if the administration is not completed then this will have an impact on the future of the bride and groom, including their descendants.